2009
DOI: 10.1111/j.1533-2500.2009.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Epidurographic Contrast Patterns with Fluoroscopic‐Guided Lumbar Interlaminar Ventral Epidural Injection

Abstract: The data showed excellent spread of contrast into the nerve root and the ventral epidural space in all patients. There were no inadvertent vascular or neural complications. LIVE approach can be an alternative way to achieve targeted ventral epidural injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Multiple prior studies have employed fluoroscopy to evaluate the dispersal pattern of injectate after interlaminar steroid injection. [6][7][8][9][10][11][12] The majority of these prior studies found the injected material remained more dorsal and unilateral in the epidural space. Assuming Lutz and colleagues to be correct, this may not be an optimal dispersal.…”
mentioning
confidence: 99%
“…Multiple prior studies have employed fluoroscopy to evaluate the dispersal pattern of injectate after interlaminar steroid injection. [6][7][8][9][10][11][12] The majority of these prior studies found the injected material remained more dorsal and unilateral in the epidural space. Assuming Lutz and colleagues to be correct, this may not be an optimal dispersal.…”
mentioning
confidence: 99%
“…Concerns regarding the safety and effectiveness of TFESI have focused attention on alternative injection routes, including lateral parasagittal interlaminar (PIL) [2], inferior foraminal (targeting the inferior aspect of the foramen) [6], retrodiscal [4,5], and lumbar interlaminar ventral epidural (LIVE) approaches [3]. Candido et al [2] found the PIL approach to be superior to TFESI with respect to ventral contrast flow and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We find their conclusion to be in error, however, as the authors in fact compared PIL with the superoposterior intervertebral foraminal placement of a transforaminal injection [1]. Furthermore, although the injection was performed at the most lateral part of the interlaminar space, the depth of spreading into the ventral epidural space anterior to the nerve root and the dural sac by this route may be inconsistent [3]; and in rare instances, the PIL technique may result in nerve injury [19]. The inferior foraminal and retrodiscal approach directly targets the origin of pain, the disc-nerve interface, but requires care to avoid disc puncture, as it is essentially a discographic needle path [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations